2007
DOI: 10.1056/nejmoa0706628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Torcetrapib in Patients at High Risk for Coronary Events

Abstract: Torcetrapib therapy resulted in an increased risk of mortality and morbidity of unknown mechanism. Although there was evidence of an off-target effect of torcetrapib, we cannot rule out adverse effects related to CETP inhibition. (ClinicalTrials.gov number, NCT00134264 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,598
8
29

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,848 publications
(1,669 citation statements)
references
References 15 publications
34
1,598
8
29
Order By: Relevance
“…Abnormal HDL-C function raised by cholesterol ester transfer protein (CETP) deficiency leads to lowering of cholesterol efflux, then reverse cholesterol transport was inhibited 29) . A clinical trial using CETP inhibitor has failed to show the protective effect for CHD, although participants in this study showed an extremely HDL-C elevation almost equivalent to very high HDL-C level in our study 30) . Some previous studies have shown mild inverse or no association between HDL-C concentrations and plasma CETP activity [31][32][33] .…”
Section: Resultscontrasting
confidence: 63%
“…Abnormal HDL-C function raised by cholesterol ester transfer protein (CETP) deficiency leads to lowering of cholesterol efflux, then reverse cholesterol transport was inhibited 29) . A clinical trial using CETP inhibitor has failed to show the protective effect for CHD, although participants in this study showed an extremely HDL-C elevation almost equivalent to very high HDL-C level in our study 30) . Some previous studies have shown mild inverse or no association between HDL-C concentrations and plasma CETP activity [31][32][33] .…”
Section: Resultscontrasting
confidence: 63%
“…The analysis cohort excluded 59 patients who were treated with an aldosterone antagonist either at randomization or during the follow‐up period. Aldosterone was measured in dal‐OUTCOMES because another CETP inhibitor, torcetrapib, had been shown to raise aldosterone levels and to promote hypertension 21, 22. After the independent Data Safety and Monitoring Board determined that dalcetrapib had no effect on aldosterone concentrations, measurements were not performed on subsequent patients enrolled in the dal‐OUTCOMES trial.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary human studies were also positive in reducing disease markers (15). In the middle of this decade, the first large scale clinical trial using a CETP inhibitor, torcetrapib, was interrupted earlier than anticipated due to high mortality rates (16). In 2007, about 40 years after the discovery of CETP activity, its molecular structure was finally resolved (17).…”
Section: Brief Highlights Of Cetp Historymentioning
confidence: 99%
“…However, the study was interrupted earlier than anticipated because of an excess of deaths and cardiovascular events in the group receiving torcetrapib. Cardiovascular disease, cancer, and infection were the main causes of death, and their rates were 40%, 70%, and 100% higher, respectively, in the torcetrapib group (16). Some adverse effects of torcetrapib, such as hypertension and increased aldosterone levels, are thought to be molecular off-target effects (48).…”
Section: Clinical Trials With Cetp Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation